2021
DOI: 10.1038/s41380-021-01394-6
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral dopamine neurotrophic factor protects and repairs dopamine neurons by novel mechanism

Abstract: Midbrain dopamine neurons deteriorate in Parkinson’s disease (PD) that is a progressive neurodegenerative movement disorder. No cure is available that would stop the dopaminergic decline or restore function of injured neurons in PD. Neurotrophic factors (NTFs), e.g., glial cell line-derived neurotrophic factor (GDNF) are small, secreted proteins that promote neuron survival during mammalian development and regulate adult neuronal plasticity, and they are studied as potential therapeutic agents for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 143 publications
1
28
0
Order By: Relevance
“…The distinct functions of the N-terminal nucleotide-binding domain (NBD) and the C-terminal substrate-binding domain (SBD) of GRP78 have been well described [ 56 ]. Similarly, the two domains of CDNF have been proposed to have distinct roles in the molecular biology of CDNF, although experimental data about these possible roles are still lacking [ 7 , 9 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distinct functions of the N-terminal nucleotide-binding domain (NBD) and the C-terminal substrate-binding domain (SBD) of GRP78 have been well described [ 56 ]. Similarly, the two domains of CDNF have been proposed to have distinct roles in the molecular biology of CDNF, although experimental data about these possible roles are still lacking [ 7 , 9 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although CDNF has been tested in phase I-II clinical trials in Parkinson’s disease patients [ 8 , 9 ], the molecular mechanism of its action is still under investigation. Despite recent publications associating CDNF with the UPR [ 27 , 29 ], the roles for CDNF in ER stress in vitro and in vivo have not been widely explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MANF and cerebral dopamine neurotrophic factor (CDNF) are proteins with pleiotropic effects on various disease models ( Lindahl et al, 2017 ; Albert and Airavaara, 2019 ; Jäntti and Harvey, 2020 ; Lindholm and Saarma, 2021 ) and form together a family of proteins (amino acid identity is 59%) ( Lindholm et al, 2007 ). MANF was originally discovered and named ARMET (arginine-rich, mutated in early-stage tumor) ( Shridhar et al, 1996 ) but was subsequently renamed MANF when the protein was first successfully isolated from a mesencephalic astrocyte cell line, and its neurotrophic properties were reported using dopaminergic neuronal cultures ( Petrova et al, 2003 ).…”
Section: Mesencephalic Astrocyte-derived Neurotrophic Factormentioning
confidence: 99%
“…Some studies have shown that neurotrophic factors such as glial cell-derived neurotrophic factor (GDNF) and brain-derived neurotrophic factor (BDNF) upregulate tyrosine hydroxylase (TH), improve movement disorders and provide neuroprotection in animal models of Parkinson’s disease ( Gash et al, 2005 ; Lindholm and Saarma, 2021 ). Katila et al (2020) indicated that by promoting the phosphorylation of tyrosine hydroxylase (TH), metformin simultaneously increases brain-derived and glial cell-derived neurotrophic factor (GDNF), thereby activating the cell survival signaling pathways.…”
Section: Metformin and Neurodegenerative Diseasesmentioning
confidence: 99%